2013
DOI: 10.1631/jzus.b1200239
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and phylogeny of Ustilago coicis

Abstract: Abstract:Ustilago coicis causes serious smut on Coix lacryma-jobi in Dayang Town, Jinyun County, Zhejiang Province of China. In this paper, ultrastructural assessments on fungus-host interactions and teliospore development are presented, and molecular phylogenetic analyses have been done to elucidate the phylogenetic placement of the taxon. Hyphal growth within infected tissues was both intracellular and intercellular and on the surface of fungus-host interaction, and the fungal cell wall and the invaginated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Analyses of rDNA ITS and LSU sequence data coupled with morphology have been used in successful taxonomical revisions of different groups of smuts in recent molecular phylogenetic studies ( Vánky & Lutz 2007 , 2010 , Bauer et al 2008 , Lutz et al 2008 , Kemler et al 2009 , Piątek et al 2011 , 2012 , 2013a , b , Lutz et al 2012a , b , Zhang et al 2013 ). In this work specimens of U. striiformis from different hosts and regions of the world were studied in terms of morphology and phylogenetic position based on nucleotide sequence data from ITS and LSU loci.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of rDNA ITS and LSU sequence data coupled with morphology have been used in successful taxonomical revisions of different groups of smuts in recent molecular phylogenetic studies ( Vánky & Lutz 2007 , 2010 , Bauer et al 2008 , Lutz et al 2008 , Kemler et al 2009 , Piątek et al 2011 , 2012 , 2013a , b , Lutz et al 2012a , b , Zhang et al 2013 ). In this work specimens of U. striiformis from different hosts and regions of the world were studied in terms of morphology and phylogenetic position based on nucleotide sequence data from ITS and LSU loci.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular phylogenetic studies by Stoll et al (2003Stoll et al ( , 2005 revealed that Sporisorium species are split into two main lineages. This finding was later confirmed by other molecular analyses (Cunnington et al 2005;Vánky et al 2006;Vánky and Lutz 2011;McTaggart et al 2012a;Shivas et al 2013;Zhang et al 2013). These two main lineages included the type species of Sporisorium (S. sorghi Ehrenb.…”
Section: Introductionmentioning
confidence: 55%
“…It is the first phylogeny focused specifically on the genus Anthracocystis, as all previous phylogenetic studies either treated Anthracocystis as a synonym of Sporisorium in a wider context of grass-infecting Ustilaginales (Cunnington et al 2005;Stoll et al 2003Stoll et al , 2005Vánky et al 2006;Vánky and Lutz 2011;Zhang et al 2013), or did not show relationships between species (McTaggart et al 2012a, c;Shivas et al 2013). The concatenated ITS+LSU dataset was constructed using only sequences that were linked to reliably identified (by smut experts) voucher specimens.…”
Section: Phylogenetic Framework For Anthracocystismentioning
confidence: 99%
“…U. trichophora was first isolated from Echinochloa colonum in Egypt by Kunze in 1830 ( 9 ). Since then, this organism has attracted little focus of research, apart from the description as a plant pathogen belonging to the Ustilaginaceae , including its phylogeny ( 10 13 ). Hence, no prior knowledge exists about molecular techniques for genetic manipulation, and the genome sequence is unknown.…”
Section: Genome Announcementmentioning
confidence: 99%